Developing organisational ethics in palliative care: A three-level approach. (March 2017) - Sandman, Lars; Molander, Ulla; Benkel, Inger
Background: Palliative carers constantly face ethical problems. There is lack of organised support for the carers to handle these ethical problems in a consistent way. Within organisational ethics, we find models for moral deliberation and for developing organisational culture; however, they are not combined in a structured way to support carers' everyday work. Research objective: The aim of this study was to describe ethical problems faced by palliative carers and develop an adapted organisational set of values to support the handling of these problems. Research design: Ethical problems were mapped out using focus groups and content analysis. The organisational culture were developed using normative analysis and focus group methodology within a participatory action research approach. Main participants and research context: A total of 15 registered nurses and 10 assistant nurses at a palliative unit (with 19 patient beds) at a major University Hospital in Sweden. Ethical considerations: The study followed standard ethics guidelines concerning informed consent and confidentiality. Findings: We found six categories of ethical problems (with the main focus on problems relating to the patient's loved ones) and five categories of organisational obstacles. Based on these findings, we developed a set of values in three levels: a general level, an explanatory level and a level of action strategies. Discussion: The ethical problems found corresponded to problems in other studies with a notable exception, the large focus on patient loved ones. The three-level set of values is a way to handle risks of formulating abstract values not providing guidance in concrete care voiced in other studies. Conclusion: Developing a three-level set of values adapted to the specific ethical problems in a concrete care setting is a first step towards a better handling of ethical problems.